Australia's Winning Edge 2012-2022 (ASC, 2012)
Australia`s international sporting reputation is formidable. Watch any major sporting event and invariably there is an Aussie in the mix. Australia`s international sporting achievements by men and women over the past 30 years have been impressive: Olympic and Paralympic champions too many to name; the America`s Cup; the Tour de France; Rugby and Cricket World Cups; world champions on bikes, in boats, on skis, jumping things, throwing things, swimming in pools and surfi ng in oceans; in summer or winter, indoor or outdoor sports; up mountains, around race-tracks and down half-pipes; throwing, kicking, netting and hitting balls of all shapes and sizes. But international competition is intensifying and improving all the time. Many other nations have now replicated Australien innovations, tapped into our expertise and made strategic investments, and as a result have become strong competitors in international sport. This is true of developed and developing nations alike. In any area of human endeavour, there is one truism — past success is no guarantee of future performance. Australias Olympic performance peaked nearly a decade ago. Since Athens in 2004 our place in the upper echelons of medal-winning nations has drifted downwards. The London Games provided clear signs that even in sports where we have had great success, there are new and re-emerging competitive challenges. Notwithstanding swimming`s extraordinary result in Beijing in 2008 (20 medals with 6 golds), the overall relative Olympic position has been trending downwards since the Sydney Games. Key statistics give a true sense of the challenge: >> Australia is winning less gold medals >> Australia is winning less medals >> Australia achieves less top-eight placings >> The conversion of top-eight placings into medals is below the average of the top 15 nations at the Games. The other measure of sustained success — annual world champions — tells a similar story and extends beyond Olympic sports. There is a trend downwards in priority sports, with 2012 likely to be the lowest result in the last 12 years. Australia has a pool of extraordinary talent that is ready to step up, and world-leading high performance expertise from coaching to nutrition to sports medicine. The Australian Sports Commission (ASC) believes that Australians want, indeed expect, to respond to this new environment — to retain the pre-eminent position in world sport and not lower the expectations. To achieve this, the Australian high performance sport sector will need to do things smarter and better, without calling on the Australian Government for additional funding given general economic pressures. Australia's Winning Edge sets out the plan and proposed actions to this end.